Lessons Learned for Future Peace Processes: Drawing insights from the 2015-2020 efforts for potential future negotiations: https://doi.org/10.55966/assaj.2025.4.1.045 - Dr. Nusrat Rehman; Erum Rizvi; Dr. Muhammad Munib Khalid (`, 2025)
Afghanistan is the land of tribal warriors who fought with every invader and contemporary examples are the Soviet Union and the USA. The organization of the Taliban which emerged on the surface of Afghanistan in 1994 and took the Government very easily and ruled across the country was also a result of the Soviet-Afghan war. Hence, Afghanistan have cultivated mistrust and uncertain conditions due to the 9/11 terrorism. After the 9/11 during Hamid Karzai regime, Afghanistan expressed her great desire for good relations with other countries which have long common border and deep social, religious and cultural connection and wants to create peace. Uncertainty in the region after 9/11 increased the high concerns and threats to the regional peace and security as terrorists have safe heavens in the tribal areas of Pakistan and along the border areas of Afghanistan. American war against terrorism and special focus on Afghanistan has developed the new dimensions. In May 2014, Obama declared to withdraw America’s troops from Afghanistan since the civilians of America were not happy and the American soldiers were being heavily slaughtered in the war. So, the absence of peace was difficult for the government since it brought about many more problems. There seemed to be no end to this war. The war proved to be a danger to not only regional peace but also national peace, the locals were conflicted and bothered as well all because of the war and lack of peace. Keywords: Peace Processes Afghanistan, regional peace, national peace